2013
DOI: 10.1186/1477-7819-11-171
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological regression of hepatocellular carcinoma with portal vein thrombosis treated with sorafenib

Abstract: Sorafenib is a molecular-targeted therapy used in palliative treatment of advanced hepatocellular carcinoma (HCC) in Child-Pugh A patients. We describe the case of a patient who presented with a large HCC in the left liver associated with portal vein thrombosis (PVT). After 9 months of sorafenib treatment, reassessment showed that the tumors had decreased in size with recanalization of the portal vein. A lateral left hepatectomy was performed and pathology showed complete necrosis of the tumor. Sorafenib can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Furthermore, neoadjuvant and/or adjuvant treatment including sorafenib and/or radiotherapy together with LR might be a promising strategy for IVCTT patients. (17,18) In a comparison between the IVCTT and mHVTT groups, while the recurrence-free survival was similar, the MST was significantly poorer in the IVCTT group. This finding can be explained by differences in the sites of recurrence (Table 3).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, neoadjuvant and/or adjuvant treatment including sorafenib and/or radiotherapy together with LR might be a promising strategy for IVCTT patients. (17,18) In a comparison between the IVCTT and mHVTT groups, while the recurrence-free survival was similar, the MST was significantly poorer in the IVCTT group. This finding can be explained by differences in the sites of recurrence (Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…However, considering that complete resection is difficult in IVCTT patients and the MSTs were similar between the LR group and the chemotherapy group (1.48 versus 1.28 years), the surgical indications for IVCTT patients require further investigation and comparison with sorafenib treatment. Furthermore, neoadjuvant and/or adjuvant treatment including sorafenib and/or radiotherapy together with LR might be a promising strategy for IVCTT patients …”
Section: Discussionmentioning
confidence: 99%
“…In the current case, the tumors exceeded 11.1 cm and there were more than 2, so the initial prognosis was expected to be bad. In addition, although sorafenib is reportedly effective on PVTT due to inhibition of vascular endothelial growth factor receptor and administration of sorafenib to HCC patients has been effective for the removal of PVTT [2], there has not been a report of the success of conventional TACE in complete removal of PVTT and HCC cure.…”
Section: Discussionmentioning
confidence: 99%
“…However, two exceptional cases leading to complete remission have been reported. One case involved HCC accompanied by PVTT treated with sorafenib [2], and the other case was diffuse HCC treated with transcatheter arterial chemoembolization (TACE) [3]. Herein, we report a case of diffuse infiltrative HCC accompanied by PVTT showing complete remission after TACE was performed twice, with no recurrence after more than 8 years of close monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the median survival of patients receiving Sorafenib is 6.5 months. The reports of Sorafenib for the treatment of HCC with PVTT has gradually increased in recent years [62,63]. Irtan S et al reported [64] two cases of locally advanced HCC with PVTT who were treated with Sorafenib during 10 and 12 months respectively and the results found that the size decrease of the main tumour, disappearance of PVTT, and normalization of AFP, which allowed curative surgical resection.…”
Section: Targeted Therapymentioning
confidence: 96%